Load balancing in cloud using prioritization based on Quality of Services (QoS) demand - Sharma, Manmohan; Jain, Vinod Kumar (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is the emerging technology that delivers the services on demand using the underline internet based software’s. It is used to store a large amount of data and provide the accessibility to that data with minimum response time. Minimum bandwidth is required to assess the stored data from anywhere. In cloud there is a shared repository of resources that the cloud service providers try to utilize efficiently. Cloud vendors lease these services to the cloud customers as per their needs or demands. Customers also pay to the vendors as per their usage of cloud services. It is beneficial for both the service provider and customer as service provider earn money leasing their resources and customers also earn using the resources which otherwise they need to purchase. Cloud computing generally uses the concepts of virtual machines (VM) and their scheduling to feed maximum customers. This paper briefs about how to improve the quality of the services provided to the customer. Here we assign priorities to the customers on the basis of certain factors like number of VMs required, request type based on pricing and association with company etc. On the basis of these factors we assign priorities to the customers and the customers are feed on the basis of this priority. Here we also included the concepts of feeding the users request from the same geographical areas with minimum distance. This will improve the overall performance and throughput of the cloud with maximum customer satisfaction.